Analysis of the Role of Teachers in Overcoming "Toxic Friendship" in Class X of Kepanjen Islamic High School - Adzra Tsabitah Nafiatul Manahil; Agnes Putri Setia; Sherina Putri Azkia; Siti Aminatuz Zuhroh (Humanities Horizon, 2024)
This research was conducted to identify the negative impacts caused by toxic friendships, both psychologically, emotionally, and socially, and to analyze various factors that can cause toxic friendships, such as personality differences, communication problems, jealousy, and past trauma, as well as to understand the negative impacts from friendships that are unhealthy and poison a person's life. The method used is a descriptive qualitative method, which means exploring and understanding the meaning of the motivational symbols of the experiences of individuals who are research subjects based on the results of observations and interviews. This method has several approaches, but we chose the phenomenological approach, which means this research aims to find the meaning of life experiences. The research results showed that people around him hated him in class. According to Kepanjen Islamic High School teachers, many are still in the class. Kepanjen Islamic High School's teachers hope this toxic friendship can be prevented and will not happen continuously. Not only that, teachers at Kepanjen Islamic High School are, of course, also involved in overcoming the occurrence of toxic friendships among teenagers, especially in class X.